Numerical treatment of frictional contact in ALE formulation for disc brake assemblies - Weidauer, Tim; Willner, Kai (Mechanical Systems and Signal Processing, 2020)
The Arbitrary-LAGRANGIAN-EULERIAN (ALE) formulation is a popular approach for finite element (FE) models governed by large rigid body movement. It facilitates the decomposition of guiding motions and relative deformation inside the model by considering the main motion of the system in the form of a material flow inside the FE mesh. This way, similar to fluid dynamics, an observer focused on spatial positions rather than individual material particles is introduced. Among others, this approach serves as an established tool in the simulation of tire rolling contact and its dynamics. However, while allowing for specific mesh refinement and simplifying issues such as finite displacements due to rigid body motions, it complicates contact computations. The history of contacting particles is not inherently tracked, demanding a special treatment of their relative displacement for evaluating their frictional contact state. The handling of stationary problems in this context is well-studied for the examples of elastic-rigid rolling contact, including inelastic material properties and thermo-mechanical coupling. This work attends to the remaining area of frictional contact in transient ALE problems and extends the methods towards elastic-elastic contact coupling in a three dimensional framework. To this end, classic Zero-Thickness contact elements, whose application in these surroundings is enabled by the relative kinematic ALE framework in the first place, are extended towards ALE compatibility. The proposed approach involves a slip-based contact formulation including inelastic slip variables and is applied in the field of disc brake assemblies. In here, several stationary and transient studies of emerging contact patterns and limit cycles are accomplished, outlining the capabilities of the proposed implementation.
CRIS-Team Scopus Importer:2020-06-09
Keywords: Arbitrary-LAGRANGIAN-EULERIAN (ALE); Disc brake; Friction oscillator; Limit cycle; Transient frictional contact; Zero-Thickness element